Design and Build Running Text Controls Using IoT - Aji Tyo Syahputra; Fauzi, Achmad; Milli Alfhi Syari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This research designs and builds an Internet of Things (IoT)-based running text control system using the P10 display module which can be controlled through the Blynk application and displays the temperature in real-time using the DHT22 sensor. The system consists of hardware such as a microcontroller, Wi-Fi module, P10 LED display, and DHT22 sensor to measure temperature and humidity. The Blynk app is used as a user interface to control the messages displayed on the P10 module and monitor the temperature data in real-time. Software development is carried out to integrate the hardware with the Blynk application and enable efficient data transmission. The test results show that this system is able to accurately display text messages and temperature data with low latency. These systems can be applied in a variety of scenarios such as public information systems, environmental surveillance, and dynamic advertising applications.